Measuring the Transition : A User's Viewon National Accounts in Russia - Koen, Vincent (IMF Working Papers; Working Paper ;, 1994)
As Russia's transition unfolds, the traditional national accounts concepts and reporting mechanisms become increasingly inadequate. As a result, the margin of error associated with basic price and quantity estimates widens substantially. A selection of key measurement and interpretation issues is discussed here, in operational rather than in methodological terms.